Hubungan Motivasi, Kegiatan dan Karakter Tempat Wisata Pada Pusaka Saujana Imogiri Yogyakarta - Fitria Puspita Rani; Hanson E. Kusuma; Angela C. Tampubolon (JURNAL MASTER PARIWISATA, 2020)
Imogiri is a cultural landscape located in Yogyakarta province that possesses both natural and cultural potency. This study aims the motivation of tourist to visit Imogiri, the activities carried out, the characteristics of places visited, and the correlation of those three factors. The study applies quantitative research methods that are exploratory and explanatory. Data collection was done through an online questionnaire and distributed to several groups (nonprobability-convenience sampling). The collected data were then analyzed quantitatively using principal component analysis, factor analysis, and multivariate correlation analysis. The analysis result found that tourist motivation to visit Imogiri consists of four categories: novelty, restoration, social and actualization. Activities carried out in Imogiri are described in six categories: active recreation, cultural recreation, passive recreation, social recreation, educational recreation, and dating. Correlation between the three variables leads to two travel categories, they are nature recreation tourism and culture recreation tourism. In nature recreation tourism, people are motivated to look for novelty and tend to do recreational activities in natural environment. While the second type, culture recreation tourism, tourist travel by the social motivation and choose to do cultural activities in places with cultural characteristic. Keywords: Tourism, Cultural landscape, Imogiri, Motivation, Activity, Place characteristic